2022
DOI: 10.1111/iwj.13956
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the efficacy of vacuum sealing drainage combined with autologous platelet‐rich plasma in the treatment of Grade 2 and Grade 3 diabetic foot ulcers

Abstract: This meta‐analysis aims to systemically evaluate the efficacy of vacuum sealing drainage (VSD) combined with autologous platelet‐rich plasma (PRP) in the treatment of diabetic foot ulcers (DFU). The China HowNet, China Biomedical Literature, VIP periodical resource integration service platform, Wanfang, Embase, Cochrane Central, and PubMed databases were retrieved using the computer. The retrieval period was up to July 2021. Randomised controlled trials on VSD combined with PRP in the treatment of DFU were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Platelet‐rich plasma (PRP) is a platelet concentrate containing a variety of growth factors and cytokines, which significantly promotes tissue and nerve repair and angiogenesis and has achieved remarkable therapeutic effects in treating chronic wounds 14 . Researchers have found that the combined use of PRP and NPWT can accelerate the healing process of chronic wounds and improve the quality of wound healing 15 . However, studies on PRP combined with NPWT for chronic wound repair are limited and have not yet reached a consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet‐rich plasma (PRP) is a platelet concentrate containing a variety of growth factors and cytokines, which significantly promotes tissue and nerve repair and angiogenesis and has achieved remarkable therapeutic effects in treating chronic wounds 14 . Researchers have found that the combined use of PRP and NPWT can accelerate the healing process of chronic wounds and improve the quality of wound healing 15 . However, studies on PRP combined with NPWT for chronic wound repair are limited and have not yet reached a consensus.…”
Section: Introductionmentioning
confidence: 99%
“…As a preferred course of treatment for people with diabetic foot ulcers, vacuum sealing drainage is what we advise based on the findings. [46][47][48][49] Limitations of the meta-analysis were as follows: there could be an assortment bias because some of the examinations that were chosen for the meta-analysis were excluded. Despite this, the omitted examination did not meet the requirements for inclusion in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complications of the two groups were not statistically different, vacuum sealing drainage has a higher effectiveness rate than standard therapy, reduces the length of hospital stay and results in larger wound size reduction. As a preferred course of treatment for people with diabetic foot ulcers, vacuum sealing drainage is what we advise based on the findings 46–49 …”
Section: Discussionmentioning
confidence: 99%
“…When the debridement has reached a certain level, the VSD technique can be chosen to isolate the wound from the outside world by means of a negative pressure suction device. The negative pressure could effectively improve wound drainage, accelerate necrotic tissue lysis and granulation tissue proliferation, establish local blood supply of the wound, and provide a good environment for wound healing of diabetes ulcers [ 97 ]. In a Chinese clinical trial, 104 patients were divided into a conventional group and VSD group, and the conventional group was treated with systemic and local anti-infection therapy and local debridement and drainage; the VSD group was treated with the VSD technique in addition to conventional treatment.…”
Section: Current Treatments For Dumentioning
confidence: 99%